The Milestone of the Citizenship Values in the Statement of 01 November 1954 " The Frameworks and the manifestations " - belaidi, rami (The Algerian Historical Journal, 2026)
This paper seeks to determine the presence of the values of citizenship in its various elements in the Statement of 01 November 1954, that was the outcome of a long struggle against the French colonialism,it made him an important addition to history of the revolution, that made it carry a number of important dimensions, Then it is an interesting ideological document within the documents of the revolution providing in all of this basic principles for the Statement about citizenship. They dealt with the most conditions and content the Statement of 01 November 1954 looking for the important values of citizenship in the Statement.